Plato's Beautiful City and the Essence of Politics - Hammond, Scott John (Lexington Books, 2020)
In Plato's political theory we discover the essence of politics, which provides the requisite lessons to understand political as it is and should be. As there is a Form of the Good, there is a Form of the Polis, discerned in Plato's philosophy and as real for us as it was for him.